Using the PDSA Cycle for the Evaluation of Pointing and Calling Implementation to Reduce the Rate of High-Alert Medication Administration Incidents in the United Christian Hospital of Hong Kong, China - Lap Fung Tsang; Wai Yi Tsang; Ka Chun Yiu; Siu Keung Tang; So Yuen Alice Sham (Patient Safety and Quality Improvement Journal, 2017)
Introduction: The present study aimed to adopt a Plan-do-Study-Act (PDSA) cycle to monitor the implementation of Pointing and Calling (P&C) in the United Christian Hospital of Hong Kong, China. Materials and Methods: A workgroup was formed to evaluate the approaches to apply P&C in high-alert medication administration using infusion and syringe devices. A series of promulgations and strategies were implemented to increase the probability of its success and sustainability. In addition, pretest and posttest evaluation was performed to monitor the incident rate associated with high-alert medication administration using infusion and syringe devices. Results:Over 100 briefing sessions were conducted in the hospital wards, and 145 senior managers, ward managers, and advanced practice nurses completed the training and assessment. In total, 217 questionnaires, which were scored based on a six-point Likert scale, were collected from 21 wards, with the response rate estimated at 26.53%. Moreover, an audit was performed to obtain 98.1-100% of the compliance rate of using the P&C for evaluation. Since June 2016, the incident rate due to inaccurate device setting decreased from 0.21 to 0.13 after the P&C implementation. Conclusion: According to the results, P&C is a simple method to facilitate the meticulous assessment of high-alert medication administration by nurses. It is recommended that further improvement be made in this regard in order to address the unidentified other areas. Of note, counter measures were proposed to strengthen P&C compliance.